Parenting Patterns with Science Literacy Skills of Four Grade Elementary School Students - Rusmaladewi, Ayu; Riastini, Putu Nanci; Sukmana, Adrianus I Wayan Ilia Yuda (Bisma The Journal of Counseling, 2024)
Most students still have low interest in science. This can be caused by parenting patterns that are less supportive and motivating. This study aims to analyze the significant relationship between parenting patterns in improving students' scientific literacy skills in the attitude aspect. This study is a type of ex post facto correlational research with a population of 98 students and a sample of 30 respondents. Sampling using stratified random sampling technique. The method and instrument for data collection in this study used a non-test method, namely a questionnaire. The data analysis technique used quantitative techniques, for hypothesis testing using simple linear regression analysis. The results of this study indicate that H0 is rejected and H1 is accepted, which means that there is a significant relationship between parenting patterns and students' scientific literacy skills because with the implementation of good parenting patterns, it will improve children's scientific literacy skills. The implications of this study are expected to be study material for teachers and parents in providing good parenting patterns for children.